High performance accelerated test methods for reliability and life time analyses of power electronic packages - Müller, Martin; Franke, Jörg (Proceedings of the Electronic Packaging Technology Conference, EPTC, 2016)
This paper describes and discusses two methods, with which highly accelerated aging tests on power electronics components can be done efficiently and with high performance. On the one hand, an alternative method of thermal shock tests with a liquid ambient medium is described. By the use of liquids as an energy transfer medium with a high heat transfer coefficient, a quick coupling of thermo-mechanical stresses at the interface of the module can be realized. So the test speed increases and the time of testing decreases. Thereby there is a shock load on the assembly even at low temperature amplitudes. In addition, a liquid-based shock system is characterized by high resource efficiency. In order to avoid any spread of the liquid medium through the transfer process of the test samples, the use of the same medium for the cold and the hot reservoir is required. In recent tests Galden® PFPE D02TS with an application range from -97 °C to +165 °C or the silicone oil WACKER® AK 35 with a maximum operating range from -60 °C to +150 °C are identified as the technically most purposeful liquids. This paper also presents a modified power cycling test equipment, with which the thermal and electrical connection of the device under test with different body variants can be realized flexibly. Further up to 20 samples can be tested simultaneously.
CRIS-Team Scopus Importer:2023-03-07